2010
DOI: 10.1111/j.1398-9995.2009.02308.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell adhesion to bronchial smooth muscle in asthma specifically depends on CD51 and CD44 variant 6

Abstract: Mast cell-BSM cell adhesion involved collagen, CD44, and CD51, particularly under inflammatory conditions. CD44v6 expression is increased in asthmatic BSM cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 45 publications
0
45
0
1
Order By: Relevance
“…CD44 is overexpressed in the lungs of rats with experimental asthma (73). In addition, CD44 variant 6 (CD44v6) is upregulated in bronchial smooth muscle of asthma patients (49). Antibody blockage of CD44 decreased mast cell adhesion to human bronchial smooth muscle cells in vitro (49), a process associated with airway hyperresponsiveness and remodeling.…”
Section: Hyaluronic Acid-binding Proteins In Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…CD44 is overexpressed in the lungs of rats with experimental asthma (73). In addition, CD44 variant 6 (CD44v6) is upregulated in bronchial smooth muscle of asthma patients (49). Antibody blockage of CD44 decreased mast cell adhesion to human bronchial smooth muscle cells in vitro (49), a process associated with airway hyperresponsiveness and remodeling.…”
Section: Hyaluronic Acid-binding Proteins In Lung Diseasementioning
confidence: 99%
“…In addition, CD44 variant 6 (CD44v6) is upregulated in bronchial smooth muscle of asthma patients (49). Antibody blockage of CD44 decreased mast cell adhesion to human bronchial smooth muscle cells in vitro (49), a process associated with airway hyperresponsiveness and remodeling. Klagas et al (67) reported a decrease in HA secretion by airway smooth muscle cells from asthma patients.…”
Section: Hyaluronic Acid-binding Proteins In Lung Diseasementioning
confidence: 99%
“…With inflammation, expression of mast cell resident CD44 (hyaluronate receptor) and CD51 (vitronectin receptor) to ECM defines mast cell adhesion to ASM. As compared to normal cells, such interactions are enhanced in cultures derived from asthmatic airways (Girodet et al, 2010). Likewise, cytokines differentially alter expression of co-stimulatory ligands such as CD40 and OX40 among ASM from airways of normal and asthmatic individuals, implying that disease pertinent mechanisms intrinsic to ASM mitigate enhanced leukocyte adherence in asthma (Burgess et al, 2005).…”
Section: Asm Markers Of Chronic Inflammationmentioning
confidence: 93%
“…As a result, mast cells are attracted by BSM and preferentially infiltrate the BSM layer of both fatal and nonfatal asthmatics [20,21]. As part of this auto-activation loop, mast cells can adhere to BSM cells [2,22,23], promoting both survival and proliferation of mast cells [24]. Mast cell activation and degranulation can be allergen dependent or independent [25][26][27][28], and can be responsible for an important extracellular deposition of inflammatory products that may facilitate the increase in BSM mass, as well as bronchial hyperresponsiveness [16,29,30].…”
mentioning
confidence: 99%
“…A sthma is a chronic inflammatory disease, characterised by the association of bronchial hyperresponsiveness, inflammation and remodelling [1][2][3]. Current medications are effective in treating acute airway narrowing and decreasing inflammation but are relatively less effective in preventing chronic structural changes [4].…”
mentioning
confidence: 99%